Elucidating Pathways and Discourses Linking Cocoa Cultivation to Deforestation, Reforestation, and Tree Cover Change in Nicaragua and Peru - Orozco Aguilar, L.A.; López Sampson, A.; Leandro M, M.E.; Robiglio, V.; Reyes, M.; Bordeaux, M.; Sepulveda, N.; Somarriba, E. (Frontiers Media, 2021)
Cocoa cultivation is labeled as a driver of both deforestation and reforestation, yet the extent of the phenomena varies at farm and landscape level and as a response to national and local contexts. In this study, we documented the main pathways and contexts behind cocoa cultivation in two sites with different histories of cocoa cultivation. We combined official statistics, land-use trajectory, satellite imagery, and the Q-analysis to explore the discourses of country experts in Nicaragua and Peru. The Q-statements were based on an analysis of a set of legal, institutional, social, and technical guidelines that the cocoa cultivation/sector influences or is influenced by. Based on the responses of national experts to 31 statements we found four discourses linking cocoa cultivation and reforestation and deforestation in each country-case study. The enabling and limiting conditions driving tree cover change were a combination of landscape configuration, governance, management/commercialization models, and farmer's knowledge. Overall, between 60 and 64% of the variance was explained by four discourse factors in each country. In Nicaragua, the conditions associated with reforestation were the cocoa-agroforestry model promoted by local organizations/NGOs, the existence of incentives, degree of technical knowledge, access to safe market, and availability of improved genetic material. The circumstances associated with deforestation were the age of the farmers, fluctuation of cocoa beans prices, low productivity of cocoa plantations, and weak legal environmental frameworks. Whereas, in Peru, the main factors connecting cocoa cultivation to reforestation were access to market, degree of experimentation in cocoa, the economic weight of cocoa on family's income, certification processes, the existence of incentives, and the level of organization/association of cocoa farmers. The elements linking cocoa farming to deforestation were the influence of stakeholders in the cocoa value chain, weak legal environmental frameworks, fluctuation of cocoa prices, the existence of private investors, and insecure land tenure rights. This article demonstrated the utility of discourse analysis, through its application to two contrasting country case-studies, to elucidate the conditions that might minimize the deforestation footprint of cocoa cultivation and maximize its role as an agent for reforestation/restoration in the agricultural landscape of cocoa-growing areas in Latin America.